Values-driven authentic leadership : essential lessons from the LeadershipWWEB podcast series - Braham, Andrew; Waller, Matthew A.; English, John (John Roy), 1958- (2022)
"In Values-Driven Authentic Leadership: Essential Lessons from the LeadershipWWEB Podcast Series, Andrew Braham, Matthew Waller, and John English examine the intersection of values, authenticity, and leadership. Drawing upon numerous conversations with a wide range of professional leaders, including several Fortune 500 CEOs, the authors identify six key opportunities for leadership growth: having a mentor, being in a group, knowing yourself, navigating transitions, being a mentor, and values and company culture. By sharing their own experiences, Braham, Waller, English, and the leaders they interview bring the facets of authentic leadership to life with personal insight. Whether you are a mentor or a mentee, a student or a professional, Values-Driven Authentic Leadership will help guide you on your own leadership journey"--
Includes bibliographical references (pages 113-114) and index.
Keywords: Leadership; Leadership